The Cumulative Exposure to High-Sensitivity C-Reactive Protein Predicts the Risk of Chronic Kidney Diseases - Jingli Gao; Aitian Wang; Xiaolan Li; Junjuan Li; Hualing Zhao; Jianjun Zhang; Jingtao Liang; Shuohua Chen; Shouling Wu (Karger Publishers, 2019)
Background and Objectives: This study was to characterize the association of cumulative exposure to increased high-sensitivity C-reactive protein (hs-CRP) with chronic kidney diseases (CKD). Methods: We included 35,194 participants with hs-CRP measured at three examinations in 2006, 2008, 2010. Participants were classiﬁed into nonexposed group (hs-CRP <3.0 mg/L in all 3 examinations), 1-exposed group (hs-CRP ≥3.0 mg/L in 1 of the 3 examinations), 2-exposed group (hs-CRP ≥3.0 mg/L in 2 of the 3 examinations), and 3-exposed group (hs-CRP ≥3.0 mg/L in 3 examinations). Cox proportional hazards models were used to assess the association of cumulative hs-CRP with incident CKD. CKD includes an estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m2 or urinary protein positive. Results: The study showed the risk of CKD as the number of years of exposure to hs-CRP increases. Participants in 3-exposed group had significantly increased CKD risk with hazard ratio (HR) (95% confidence interval, CI) of 1.70 (1.49-1.93), in comparison with 1.47 (1.34-1.62) for participants in the 2-exposed group, and 1.08 (1.00-1.16) for those in the 1-exposed group (p < 0.01); meanwhile, the similar and significant associations were also observed for eGFR <60 mL/min/1.73 m2, proteinuria positive, in participants of the 3-exposed group in comparison with the nonexposed group, with respective HRs (95% CI) of 1.27 (1.01-1.58) and 2.27 (1.87-2.76). Conclusions: Cumulative exposure to hs-CRP was associated with a subsequent increased risk of CKD and was of great value to risk prediction.